2011
DOI: 10.5897/ajb10.2336
|View full text |Cite
|
Sign up to set email alerts
|

Controlling bruchid pests of stored cowpea seeds with dried leaves of Artemisia annua and two other common botanicals

Abstract: Insecticidal activities of dried Artemisia annua L. leaves were evaluated against bruchid (Callosobruchus maculatus F.) pests in comparison with those of Azadirachta indica, Ocimum gratissimum and a conventional grain storage insecticide, Actellic® 2% dust. Each treatment was added to a mixture of 250 g cowpea seeds and 25 adult bruchids and laid out in a completely randomized design with four replicates. Irrespective of the concentration tested, all three plant materials significantly (P < 0.05) increased mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 27 publications
1
11
2
Order By: Relevance
“…However, no significant difference exists between V. amygdalina and A. indica leaf powder and between V. amygdalina leaf powder and the control. In contrast to the findings of Brisibe et al, [51] who reported that, of the three botanical pesticides (A. annua; A. indica and Open Access Library Journal O. gratissimum) tested, the highest adult insect mortality rate was recorded in the treatment with the highest concentration (20 g/250g cowpea seeds) of dried and pulverized leaves respectively. They reported that at the concentration of 5 g of the tested botanicals, no significant difference existed among them but in the present study, the treatment with the highest concentration of 5 g of the leaf powders of A. indica on 30 g of cowpea seeds caused a significant difference in the mortality of C. maculatus.…”
Section: Discussioncontrasting
confidence: 85%
“…However, no significant difference exists between V. amygdalina and A. indica leaf powder and between V. amygdalina leaf powder and the control. In contrast to the findings of Brisibe et al, [51] who reported that, of the three botanical pesticides (A. annua; A. indica and Open Access Library Journal O. gratissimum) tested, the highest adult insect mortality rate was recorded in the treatment with the highest concentration (20 g/250g cowpea seeds) of dried and pulverized leaves respectively. They reported that at the concentration of 5 g of the tested botanicals, no significant difference existed among them but in the present study, the treatment with the highest concentration of 5 g of the leaf powders of A. indica on 30 g of cowpea seeds caused a significant difference in the mortality of C. maculatus.…”
Section: Discussioncontrasting
confidence: 85%
“…The pungent and offensive odour of these plant materials may have caused an unconducive environment for the insects to reproduce. The results of this study are in total conformity with results obtained by Ebiamadon et al, 2011. Ebiamodon et al, 2011 why controlling bruchid pests of stored cowpea seeds using dried leaves of bitter leaf reported that the insecticidal activity of bitter leaf (vernonia amygdalina) was because it contained fairly high levels of bioactive constituents with fumigant activity which made it to have potent insecticidal properties. Also, Schmuhener and Ascher (1984), while working on another botanical, reported that the insecticidal activities of neem (Azadirachta indica) was a result of the presence of highly oxidized tetrapenoids, azadirachtin, salanin and other active products that posses repellant, antifeedant and growth disruptive properties against various insect species particularly C. maculatus.…”
Section: Resultssupporting
confidence: 91%
“…Moses and Dorathy [43] reported that bitter leaf gave the best protection against cowpea weevil when compared with garlic and ginger. They also reported that the significant difference (P < 0.05) obtained in the mortality of C. maculatus by comparing the efficacy of A. indica leaf powder with the control is an indication that A. indica leaf powder has some insecticide properties capable of controlling pests of stored Brisibe et al [45] reported that, of the three botanical pesticides (A. annua; A. indica and O. gratissimum) tested, the highest adult insect mortality rate was recorded in the treatment with the highest concentration (20 g/250g cowpea seeds) of dried and pulverized leaves respectively. They reported that at the concentration of 5 g of the tested botanicals, no significant difference existed among them but in the present study, the treatment with the highest concentration of 5 g of the leaf powders of A. indica on 30 g of cowpea seeds caused a significant difference in the mortality of C. maculatus.…”
Section: Discussionmentioning
confidence: 95%